2017
DOI: 10.3892/etm.2017.4458
|View full text |Cite
|
Sign up to set email alerts
|

KATP channels in high glucose-induced rat mesangial cell proliferation and release of MMP-2 and fibronectin

Abstract: ATP-sensitive potassium (KATP) channels are well characterized in cardiac, pancreatic and many other muscle cells. The purpose of this study was to determine if KATP channels play a role in diabetic nephropathy (DN). In the present study, functional expression of the KATP channel was examined in rat mesangial cells with or without high glucose (HG) stimulation. The mesangial cell proliferation and the release of matrix metalloproteinase (MMP)-2 and fibronectin in response to high glucose with a selective opene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…Studies performed in the heart and pancreas have shown that diazoxide can directly affect Erk1/2 phosphorylation and matrix metalloproteinase activity. 40 , 41 The Erk1/2 pathway is a strong modulator of matrix metalloproteinases, which have been shown to be necessary for ECM turnover in the trabecular meshwork and uveoscleral outflow pathway in association with IOP reduction. 42 , 43 Additionally, the K ATP channel opener iptakalim was shown to reduce accumulation of collagen IV and fibronectin in the renal vasculature of a rat hypertension model by inhibiting TGFβ1 expression and normalizing matrix metalloproteinase 9 and TIMP1 function.…”
Section: Discussionmentioning
confidence: 99%
“…Studies performed in the heart and pancreas have shown that diazoxide can directly affect Erk1/2 phosphorylation and matrix metalloproteinase activity. 40 , 41 The Erk1/2 pathway is a strong modulator of matrix metalloproteinases, which have been shown to be necessary for ECM turnover in the trabecular meshwork and uveoscleral outflow pathway in association with IOP reduction. 42 , 43 Additionally, the K ATP channel opener iptakalim was shown to reduce accumulation of collagen IV and fibronectin in the renal vasculature of a rat hypertension model by inhibiting TGFβ1 expression and normalizing matrix metalloproteinase 9 and TIMP1 function.…”
Section: Discussionmentioning
confidence: 99%